New syllabus primary mathmetics work book 3A 2nd edition - DR YEE, FOONG PUI (Karachi: Oxford university press, 2024)
The Primary Mathematics Workbook 3A (2nd Edition), based on the Singapore Math approach, serves as a companion to the Primary Mathematics 3A Textbook. It introduces third-grade students to foundational mathematical concepts, emphasizing problem-solving skills through the concrete-pictorial-abstract method. This workbook covers essential topics such as addition, subtraction, multiplication, division, fractions, measurements, money, and time. Through varied exercises and visual aids, students progress from understanding math concepts in tangible forms to applying abstract reasoning in solving practical problems. The workbook aims to enhance critical thinking, mental arithmetic, and a deep understanding of mathematical principles.
Keywords: Oxford mathematics